STRATEGI KOMUNIKASI PEMASARAN MATAYA ART AND HERITAGE PADA EVENT “PAMERAN KAIN NUSANTARA’’ - Deky Seto Aji; Musta’an Musta’an (ITB AAS INDONESIA Surakarta, 2021)
This research is a case study because this research uses a qualitative approach and involves case study research. The result of this research is descriptive analysis. Sources of data in this study are words and actions obtained from informants connected to research, while documents or other written sources are additional data. The data analysis technique used interactive analysis. Analysis was carried out on all data obtained from interviews and documentation. The results ofthe research include History of the establishment of Mataya Arts And Heritage, Organizational Structure of Mataya Arts And Heritage, Management of Mataya Arts And Heritage, Vision and Mission of Mataya Arts And Heritage, Cultural Event Activities